2021
DOI: 10.3389/fsurg.2021.738421
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Retzius-Sparing Robot-Assisted Radical Prostatectomy vs. Conventional Robot-Assisted Radical Prostatectomy: An Up-to-Date Meta-Analysis

Abstract: Background: The Retzius space-sparing robot-assisted radical prostatectomy (RS-RARP) has shown better results in urinary continence, but its efficacy and safety compared to conventional robot-assisted radical prostatectomy (c-RARP) remain controversial.Material and Methods: A research was conducted in Medline via PubMed, Cochrane Library, EMBASE, and Web of Science up to January 4, 2021, to identify studies comparing RS-RARP to c-RARP. We used RevMan 5.3 and STATA 14.0 for meta-analysis.Results: A total of 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
0
9
0
3
Order By: Relevance
“…Additionally, a report showed that compared with C-RARP, RS-RARP showed better recovery of continence, shorter console time, and a lower incidence of hernia. Although there was no significant difference in overall PSM, we suggest that the surgeon should be more careful if the lesion is in the anterior prostate 23 . However, some studies are also controversial.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Additionally, a report showed that compared with C-RARP, RS-RARP showed better recovery of continence, shorter console time, and a lower incidence of hernia. Although there was no significant difference in overall PSM, we suggest that the surgeon should be more careful if the lesion is in the anterior prostate 23 . However, some studies are also controversial.…”
Section: Discussionmentioning
confidence: 56%
“…Although there was no significant difference in overall PSM, we suggest that the surgeon should be more careful if the lesion is in the anterior prostate 23 . However, some studies are also controversial.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Notably, more than 20 publications in the latest 4 years were comprehensive, narrative, systematic, and or meta-analytic literature reviews of the studies comparing anterior (or standard) to posterior (or Retzius-sparing) prostatectomy. Table 2[29 ▪▪ ,30–33,34 ▪▪ ,35–39,40 ▪ ] summarizes the most important findings of the 11 systematic reviews, confirming the role of RS-RARP in providing better immediate urinary continence recovery. Some of these reviews confirmed the advantage of RS-RARP on late continence recovery.…”
Section: The (False?) Problem Of Positive Surgical Marginsmentioning
confidence: 67%
“…Retzius-sparing RARP (RS-RARP) developed by Galfano et al showed no difference in postoperative erectile function, although good postoperative urinary continence was verified [5,37]. Several meta-analyses also reported that postoperative erectile function was equivalent between conventional and RS-RARP [38][39][40]. Blood flow to the penis is considered to be supplied by the IPA and the accessory pudendal artery (APA) [41].…”
Section: Surgical Technique Including Nerve Sparingmentioning
confidence: 99%